PENGEMBANGAN E-MODULE BERBASIS SCIENCE TECHNOLOGY SOCIETY (STS) PADA MATERI SISTEM IMUN DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA - Noviani Noviani; Himmatul Hasanah (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to produce an e-module based on Science Technology Society (STS) on the immune system material that is effective in improving critical thinking skills of grade XI high school students. This type of research is Research and Development (R&D) with the ADDIE research model (Analysis, Design, Development, Implementation, and Evaluation). The sampling technique used in this study was cluster random sampling with a research design of non-equivalent pretest and posttest control group design. The e-module was assessed for its feasibility and practicality by experts and limited trials. The results of this study indicate that the e-module is declared feasible and the results of the limited test of the use of the e-module are declared practical. The results of the large-scale test show that in the experimental class by implementing the STS-based e-module there was an increase in critical thinking skills with an average posttest score of 81.53 with the results of the gain score test on the medium criteria. While the control class also experienced an increase in critical thinking with an average posttest score of 77.00 with the results of the gain score test on the low criteria